A case of CREST syndrome associated with primary biliary cirrhosis - OHGO Noriko; NOMURA Akemi; UEMURA Hiroyuki; DOI Akira; KOMORI Hideshi; SOH Yoshiro (Skin research, 1989)
A 44 year-old female case of CRESTsyndrome with primary biliary cirrhosis was described. Since 16 years ago, she had Raynaud's phenomenon, sclerodactylia and rash affecting her trunk and extremities, In 1981, she complained of difficulty in swallowing food. Bariumenema showed depressed esophageal motility, esophageal ulcer and dilatation in 1984. Hemangioma-like telangiectasia on the fingers and face appeared in 1984, then calcinosis cutis of her left arm was seen in 1988. Laboratoryfindings were anti-centromere antibody of 1: 5120, anti-mitochondrial antibody of 1: 640, IgM value of 564mg/dl and obstructive liver dysfunction. Liver needle biopsy specimen was compatible with early stage of primary biliary cirrhosis. D-penicillamine and predonisone were effective for her eruption but liver function became gradually worse. 44歳, 女性の原発性胆汁性肝硬変に, 手指硬化症, Raynand現象, 食道の拡張と蠕動運動の低下, 手, 顔面の血管腫状のtelangiectasiaおよびcalcinosis cutisなどの症状を示す完全型CREST症候群を合併した1例を報告した。躯幹, 四肢に汎発性限局性強皮症を思わせる硬化性紅斑が認められたが, 典型的なlilac ringは伴わず, 永年消長をくり返した。抗セントロメア抗体, 抗ミトコンドリア抗体陽性, Ig M高値。皮膚の組織像で表皮は一部acanthosis, 基底細胞でのメラニンの増生, 浮腫性変化, 表皮下層にヒアリン小体もみられ, 真皮膠原線維の結節状の増生を伴ったが, 汗腺, 毛嚢の減少は認められなかった。